Incidence of fiscal policy on territorial development in Costa Rica - Hartley Ballestero, Marjorie (2022)
The contribution of environmental fiscal instruments (taxes and fees) used in Costa Rica to finance conversation activities on biodiversity is analyzed. The collection of fiscal income is estimated, as well as its distribution in the different projects in favor of the environment. These tax revenues have contributed to limitations and deficiencies in forest recovery and the protection of bodies of water, mostly located in rural areas, and have incorporated women and indigenous people in these economic and conservation activities. Thus, environmental fiscal policy has contributed moderately to the sustainable development of these rural territories, which makes it urgent for fiscal policy to identify new environmental fiscal instruments that redirect towards a resilient and inclusive development.